Transcriptomic Analysis Links Eosinophilic Esophagitis and Atopic Dermatitis - Doucet-Ladevèze, Rémi; Holvoet, Sébastien; Raymond, Frédéric; Foata, Francis; Hershey, Gurjit K. Khurana; Sherrill, Joseph D.; Rothenberg, Marc E.; Blanchard, Carine (Frontiers in Pediatrics, 2019)
Background: Eosinophilic esophagitis (EoE) is commonly associated with concomitant atopic diseases including atopic dermatitis (AD) and allergic airway (AA) diseases including asthma. Despite this link and the shared pathologic features across these three disorders, detailed analyses of the unifying molecular pathways are lacking. Objectives: We sought to investigate the mRNA expression profile overlap between EoE, AA, and AD and to identify the involvement of interleukin 13 (IL-13) in modulating gene expression. Methods: Whole-genome mRNA expression analyses were performed on tissue specimens (biopsies or nasal brushes) from patients with EoE, AD, and AA, and IL-13-stimulated primary human epithelial cells from the esophagus, the skin, and the airways. Results: By human disease expression profiles, EoE evidenced a significantly higher overlap (p = 0.0006) with AD (181 transcripts; 10%) than with AA (124 transcripts, 7%). Only 18 genes were found to be commonly dysregulated among the 3 diseases; these included filaggrin, histamine receptor H1, claudin 1, cathepsin C, plasminogen activator urokinase receptor, and suppressor of cytokine signaling 3. Ontogenetic analysis revealed a common immune/inflammatory response among the three diseases and a different epithelial response (epidermal cell differentiation) between EoE and AA. The overlap between the IL-13–stimulated epithelial cell transcriptome and the respective disease transcriptome was 22%, 9%, and 5% in EoE, AD, and AA, respectively, indicating a greater involvement of the IL-13 pathway in EoE than AA (p = 0007) or AD (p = 0.02). Conclusion: EoE, AD, and AA share a common set of disease-specific transcripts, highlighting common molecular etiology. Their comparative analysis indicates relatively closer relationships between EoE and AD, particularly centered around IL-13–driven pathways. Therefore, these findings provide an increased rationale for shared therapeutic strategies.